EFFECTS OF FOREIGN DIRECT INVESTMENT ON THE ECONOMY AND ENVIRONMENT - Bukša, Tomislav; Bukša, Juraj; Kosovac, Ivana (Journal of process management and new technologies, 2022)
Classical theories linking increased CO2 emissions to a country's economic development supported by foreign direct investment in industrial plants, coking plants, ironworks, shipbuilding, and other heavy industries marked the 20th century, with large MNCs seeking refuge in underdeveloped economic development. The second millennium of Croatia began with deindustrialization, both due to the extinction of large state-owned industrial losers and due to transformation and privatization, where the interest of capital was in the financial and tourism sectors. This does not mean that FDI was not present, but the expected greenfield investments were missing, especially after joining the EU. To what extent FDI has influenced the increase in carbon emissions is the subject of research in this paper.